A influência da marca nas escolhas de compra dos consumidores em condição de esgotamento do ego (ego depletion) - Bednaski, Adriano Viana (2015)
In addition to performing a number of decisions daily, an individual living in a world where you need greater control of emotions, impulses and thoughts. All these activities require an intense self-control, which leads to a condition of the Ego Depletion - Ego Depletion (BAUMEISTER et al., 2007). This condition is characterized by a reduced ability to exercise self-control, causing a temporary reduction in the willingness to engage in a next task (BAUMEISTER, 1998). When putting in a consumer choice situation at the end of the day, an individual can make purchases differently than you would if the activity was held in the morning. This relationship of purchase has been studied by several authors (BAUMEISTER, 2002b; Vohs, 2006; Vohs and Faber, 2007; HOFMANN et al., 2008). The purpose of this work was to understand the effects that a brand has on individuals in a state of ego depletion. For this there were three independent experiments with 148 college students from both institutions of Brazilian higher education. Empirical data indicate that individuals, when the Ego Depletion conditions, buy more branded products than individuals who are not exhausted. And even if the mark is well-known, they still buy more branded products as compared to a mark not recognized, even if the choice of brand is less advantageous in the rational assessment of cost / benefit. The results indicate the brand moderating effect on purchases consumers with Ego Depletion, and also a moderating effect of brand awareness on purchases of these individuals.